Evaluation of the implementation of smart specialisation strategy in Lithuanian industry - Augustinaitis, Arūnas; Kaivo-oja, Jari; Lauraeus, Theresa; Kiškienė, Austė; Bzhalava, Levan; Roth, Steffen (Journal of Business Economics and Management, 2022)
This article provides data-driven analyses of Lithuanian foreign trade activities. We combine Herfindahl-Hirschman Index (HHI) and Lauraéus-Kaivo-oja Index (LKI) measures to identify key changes and trends in export and import structures of the Lithuanian economy. The findings suggest that the export and import portfolios of the Lithuanian economy have been successfully diversified and the Lithuanian Smart Specialisation Strategy (S3) successful implemented in years 2015 through 2020. Presented in the form of HHI and LKI time series, our findings and the corresponding conclusions will be relevant to both the Lithuanian export and import industry and to industrial and economic policymakers in Lithuania and in international export and import agencies.